(untitled) (World Economics and Finance Bulletin, 2025)
This research aims to explore the role of artificial intelligence, specifically the ChatGPT model, in enhancing the understanding and analysis of financial statements using innovative and advanced methods. It highlights how this technology can be utilized to analyze financial data and extract strategic insights that contribute to enhancing the quality of financial and administrative decisions. The research relies on an in-depth analytical methodology that combines theoretical studies and practical applications of the use of artificial intelligence tools in processing financial statements. The results showed that the use of artificial intelligence significantly contributes to improving the accuracy of financial analysis, accelerating processes, and revealing financial patterns and trends that may not be apparent using traditional methods. It also enhances organizations’ ability to predict financial performance and plan strategically more efficiently. The research recommends investing in the development and adoption of artificial intelligence technologies in financial analysis and raising awareness among institutions and academic institutions of their importance and pivotal role in achieving transparency, reducing human error, and enhancing the efficiency of financial resource management